Contributions to the investigations of Lascar strong types in simple theories - Lewitzka, Steffen (2003)
Lewitzka, Steffen; José Guerra Barreto de Queiroz, Ruy. Contributions to the investigations of Lascar strong types in simple theories. 2003. Tese (Doutorado). Programa de Pós-Graduação em Ciência da Computação, Universidade Federal de Pernambuco, Recife, 2003.